A Validation of the Real Zeros of the Riemann Zeta Function via the Continuation Formula of the Zeta Function - O.O.A. Enoch; F.J. Adeyeye (Journal of Basic & Applied Sciences, 2012)
In this paper, the analytic continuation formula of the Riemann zeta function is presented as a function of t2n, thus validating Riemann’s claim that ε(t) allows itself to be developed in the power of t2. It is also shown that the root of ε(t) is always real. A theorem to validate the real roots is established.